Restoration of Citropsis articulata, a Species at Risk from Medicinal Overharvesting in a Ugandan Rainforest Reserve - William Olupot (International Journal of Forestry Research)
Citropsis articulata, the African cherry orange, is considered to be threatened in Ugandan forests as a result of its purported aphrodisiac properties. This study, part of an ongoing effort to address restoration needs of Mabira Central Forest Reserve in Uganda, demonstrates the feasibility of restoring depleted C. articulata populations using seedlings transplanted from nursery-grown seeds. Phenology of 20 Mabira forest plants was monitored with the aim of collecting seeds. One hundred and fifty-six ripe fruits were collected, and 233 of the extracted seeds were planted in pots in a nursery during January–March 2019. During November-December 2019, seedlings were planted near the sites from which fruits were collected. Seed germination success rate was 89%, and fifteen months after transplanting, in situ survival was 100%. These results suggest that depleted C. articulata populations may be restored in situ using nursery-grown seeds.